Being and symptom: The intersection of sociology, lacanian psychoanalysis and continental philosophy - ÖĞÜT, SÜHEYP (academica press, 2020)
In this book, I focus on Hobbes in terms of his explanation of sovereignty. Why? Because, sovereignty, demystified by Hobbes, is not just a political process. When it manifests itself within ousia, it reveals itself as metaphysics. When it manifestsitself within epistemology, it reveals itself as transcendentality. When it manifests itself within phenomenology, it reveals itself as dialectics. When it manifests itself within ontology, it reveals itself as hermeneutical phenomenology. When it manifests itself within sociology, it reveals itself as archaeology. When it manifests itself within psychology, it reveals itself as psychoanalysis. When it manifests itself within language, it reveals itself as deconstruction. When it manifests itself within capitalism, it reveals itself as neo-liberalism. When it manifests itself within (post)modernity, it reveals itself as pornography. When it manifests itself within existence, it reveals itself as privacy. When it manifests itself within economics, it reveals itself as game (theory). When it manifests itself within reality, it reveals itself as ideology-critique. Hence, the radical theory of sovereignty created by Hobbes is a sort of M Theory, the very unconscious of the aforementioned theories. This unconscious is always composed of four elements:1) dunamis, adunamis, energeia, entelecheia;2) state of nature, the Leviathan, state of politics, social contract3) noumena, transcendental subject, phenomena, time-space4) nature, geist, idea, notion5) sein, dasein, seiende, welt6) resistance, subject, power, dispositive7) mother, phallus, subject, the-name-of-the-father8) jouissance, sinthome, symbolic order, ideological fantasy9) being, différance, language, other10) privation, private, privacy, prohibition11) prisoners\" dilemma, police, equilibrium, offer12) signified, signifier, sign, significationThrough this theory, I analyze the unconscious of our social (sexual) relations, subjectivities and politics.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)